1996
DOI: 10.1006/qres.1996.0003
|View full text |Cite
|
Sign up to set email alerts
|

An Alluvial Surface Chronology Based on Cosmogenic36Cl Dating, Ajo Mountains (Organ Pipe Cactus National Monument), Southern Arizona

Abstract: A chronology of alluvial surfaces on piedmont slopes below the western Ajo Mountains, southern Arizona, has been obtained using cosmogenic 36Cl accumulation and AMS radiocarbon dating. The apparent 36Cl ages of individual boulders range from 520,000 to 13,000 yr, and the 14C ages of organic material in the two young terraces are 2750–2350 and 17,800 cal yr B.P. The sequence of36Cl ages is consistent with the apparent stratigraphic order, but groupings of similar ages for different surfaces appear to result fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Squares denote mean value, lines denote one standard deviation from the mean, and bars denote an age range. Using j = 1 m 2 / ky, the photometric method agrees with the Simpson (1991) age estimates while the ground-survey method agrees with Liu et al (1996). Vegetation is thought to be the main discrepancy between the photo and survey methods.…”
Section: Applicability Of Simple Linear Diffusionsupporting
confidence: 53%
See 3 more Smart Citations
“…Squares denote mean value, lines denote one standard deviation from the mean, and bars denote an age range. Using j = 1 m 2 / ky, the photometric method agrees with the Simpson (1991) age estimates while the ground-survey method agrees with Liu et al (1996). Vegetation is thought to be the main discrepancy between the photo and survey methods.…”
Section: Applicability Of Simple Linear Diffusionsupporting
confidence: 53%
“…Simpson (1991) used soil-carbonate morphology to place AJ1 at early to middle Pleistocene (1.8 Ma to 900 ka) and AJ2 at latest Pleistocene to middle Holocene (300 to 50 ka). The cosmogenic 36 Cl study of Liu et al (1996) concluded that AJ1 stabilized at 440 ka and was possibly reactivated between 230 and 330 ka. AJ2 was dated to between 100 and 180 ka.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…While promising, these methods provide model ages that rely on parameters that are partially known: erosion rates, nuclide inheritance and the complex history of the measured clasts (e.g., Clapp et al, 2000;Hancock et al, 1999;Liu et al, 1996;Matmon et al, 2003;Putkonen and Swanson, 2003;Repka et al, 1997;Watchman and Twidale, 2002).…”
Section: Introductionmentioning
confidence: 99%